Pola Hidup Sehat Mahasiswa Magister Manajemen Pendidikan Islam Institut PTIQ Jakarta Perspektif Gerakan Masyarakat Hidup Sehat (GERMAS) - Siskandar Siskandar; Ahmad Zain Sarnoto; Etika Nailur Rahma (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
The purpose of this study is to analyze healthy life self-management of master students and to find a Healthy Lifestyle Perspective Healthy Living Movement (GERMAS). The method used in this research is a qualitative descriptive with fenomenolgy approach. While the data collected in the ways of interviews, observation, documentation and data analysis techniques in the ways of Data Reduction, and Data Display. Based on the results of the research, it is known that self-management is a healthy life of PTIQ Jakarta management master students, mostly done well by students, by implementing a Healthy Lifestyle according to the steps of the Healthy Living Society Movement (GERMAS), Informants who do not apply a Healthy are due to several factors, both factors that influence the formation of attitudes and behavior formation.